Mapeamento do processo de gerenciamento dos resíduos da construção civil em Fortaleza - Leal, Denise Alves (2019)
Civil construction is one of the main causes of environmental impacts, not only due to the consumption of natural resources, but also due to the indiscriminate disposal of Construction and Demolition Waste (CDW). Thus, this study sought to map the flow of CDW processes – from generation to reinsertion in the market or final disposal – and hierarchize the waste according to its reuse priority. The research methodology was divided into two parts: the first step was to conduct semi-structured interviews with public and private sector representatives of the CDW management process; the second stage was attended by two technical specialists and a construction company for the creation and application, respectively, of a CDW hierarchy instrument. The research resulted in the characterization of the individual and collective activities of local companies involved in the reverse logistics of the CDW and the stakeholders of the process, in addition to listing their main obstacles. The first step of the research proved the need to study the CDW reverse chain to propose suitable solutions to the obstacles listed by its participants. The second step served to reiterate the results obtained in the first one, pointing out the residues with the greatest need for reuse, namely class A waste, wood and gypsum. The hierarchization was relevant because it enabled the prediction of the residues with greater need of treatment in an impartial and direct way. It is concluded that there is a need for the creation of new action plans, incentive policies, laws and sanctions application that allow the progress of sustainable performance in construction, as well as greater awareness of stakeholders, reduction of bureaucracy for the implementation of recycling plants, incentives for producers and buyers of recycled products, greater supervision of sorting, transportation and final destination of CDW.